A fast and frugal algorithm to strengthen diagnosis and treatment decisions for catheter-associated bacteriuria. - Aanand D Naik; Felicia Skelton; Amber B Amspoker; Russell A Glasgow; Barbara W Trautner (PLoS ONE, 2017)
OBJECTIVES:Guidelines for managing catheter-associated urinary tract infection (CAUTI) and asymptomatic bacteria (ASB) are poorly translated into routine care due in part to cognitive diagnostic errors. This study determines if the accuracy for CAUTI and ASB diagnosis and treatment improves after implementation of a fast and frugal algorithm compared with traditional education methods. MATERIALS AND METHODS:A pre and post-intervention with contemporaneous comparison site involving inpatient and long term care wards at two regional Veterans Affairs Systems in United States. Participants included 216 internal medicine residents and 16 primary care clinicians. Intervention clinicians received training with a fast and frugal algorithm. Comparison site clinicians received guidelines education. Diagnosis and treatment accuracy compared with a criterion standard was assessed during similar three-month, pre- and post-intervention periods. Sensitivity, specificity, and likelihood ratios were compared for both periods at each site. RESULTS:Bacteriuria management was evaluated against criterion standard in 196 cases pre-implementation and 117 cases post-implementation. Accuracy of bacteriuria management among intervention participants was significantly higher, post-implementation, than those at the comparison site (Intervention: positive likelihood ratio (LR+) = 8.5, specificity = 0.89, 95% confidence interval (CI) = 0.78-1.00; comparison: LR+ = 4.62, specificity (95%CI) = 0.79 (0.63-0.95). Further, improvements at the intervention site were statistically significant (pre-implementation: LR+ = 2.1, specificity (95%CI) = 0.60 (0.50-0.71); post-implementation: LR+ = 8.5, specificity (95%CI) = 0.89 (0.78-1.00). At both sites, there were similar improvements in negative LR from pre- to post-implementation: [Intervention site = 0.28 to 0.08; comparison site = 0.13 to 0.04]. Inappropriate management of ASB declined markedly from 32 (40%) to 3 (11%) cases at the intervention site. CONCLUSIONS:A fast and frugal algorithm improves diagnosis and treatment accuracy for CAUTI and reduces inappropriate treatment of ASB. Fast and frugal algorithms that realign diagnostic intuitions and treatment norms can enhance translation of evidence into practice.